EFFORTS TO PREVENTING MALARIA IN COMMUNITIES NOLOKLA VILLAGE, EAST SENTANI DISTRICT, JAYAPURA REGENCY - Mofu, Renold M.; Wiwiek Mulyani; Andreas C. Ayomi (Pusat Riset dan Inovasi Nasional, 2023)
Malaria is one of the public health problems that can lead to death. Papua is one of the highest contributors to malaria cases. Therefore, the community needs to make efforts to prevent malaria. This study aims to obtain information about malaria prevention efforts carried out by the community in Nolokla Village. This type of research is descriptive. The sampling technique uses Stratified Random Sampling. A sample of 98 households was selected by tier. Data were collected using questionnaires and observation sheets (cheklists). The results showed that those who did not meet the requirements in this study were mosquito shelters (100%), the habit of going out at night (86%), mosquito repellent (77%), the habit of opening the door at night (78%), and for those who met the requirements, namely the use of mosquito nets (89%), the use of gauze wire in house ventilation (65%), the use of ceilings 64%, home hygiene efforts (71%), the habit of opening windows at night (100%). The prevention carried out by the people of Kampung Noloklais the use of mosquito nets in their bedrooms, the use of mosquito screen wire in the ventilation of the house, the place where mosquitoes are still found around the house and the use of health services tends to be rarely used by the community. For this reason, health workers, especially sanitation and health promotion workers, are more active in holding counseling and inviting village elements to protect the environment.